Blockchain as Electronic Evidence Against Crypto Crimes in Indonesia - Gorizky; Supardi (Media Iuris, 2024)
In the context of digital security, the utilization of blockchain technology as a means of evidence against crypto crimes has become an exceedingly crucial topic. This research elucidates whether the admissible evidence tool stipulated in Article 184 paragraph (1) of the criminal procedural law encompasses proof relating to crypto crimes and how the decentralized structure and transparent nature of blockchain can aid in furnishing accurate and credible evidence pertaining to crypto crimes. This study offers profound insights into the potential of blockchain concerning evidence provision and prevention of crypto crimes. The author employs normative research, a process aimed at uncovering legal rules, principles, and doctrines to address legal issues encountered. Based on the discussion, it can be concluded that blockchain can serve as an electronic evidence tool in crypto crimes. Aligned with the decentralized and transparent nature of blockchain, it can provide precise and permanent data.